2020
DOI: 10.3390/ijms21145157
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Regulation of Human Multidrug and Extrusion Transporters hMATE1 and hMATE2K

Abstract: Vectorial transport of organic cations (OCs) in renal proximal tubules is mediated by sequential action of human OC transporter 2 (hOCT2) and human multidrug and toxic extrusion protein 1 and 2K (hMATE1 and hMATE2K), expressed in the basolateral (hOCT2) and luminal (hMATE1 and hMATE2K) plasma membranes, respectively. It is well known that hOCT2 activity is subjected to rapid regulation by several signaling pathways, suggesting that renal OC secretion may be acutely adapted to physiological requirements. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The MDCK cells are a very important system for studying epithelial polarization [34]. Indeed, there are several works using MDCK cells as the expression system for hOCT2 and other organic cation transporters [35][36][37]. Usually, MDCK cells are cultured on filters to allow distinct experimental access to basolateral and apical membrane domain compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDCK cells are a very important system for studying epithelial polarization [34]. Indeed, there are several works using MDCK cells as the expression system for hOCT2 and other organic cation transporters [35][36][37]. Usually, MDCK cells are cultured on filters to allow distinct experimental access to basolateral and apical membrane domain compartments.…”
Section: Discussionmentioning
confidence: 99%
“…In further experiments, acute regulation of the ASP + uptake (1 and 4 µM ASP + for hOCT2-HEK and hOCT2-MDCK cysts, respectively) by short-time incubation (10 min) with 10 µM aminogenistein, 5 µM calmidazolium or 10 µM TBBz as inhibitors of p56 lck tyrosine kinase, Ca 2+ -calmodulin or CKII, respectively, was measured. These inhibitors at these concentrations were chosen because they had already been demonstrated to be effective in regulating hOCT2 activity [37,56]. Solvents (DMSO or ethanol) at the concentration used in the regulation experiments did not change the ASP + uptake (not shown).…”
Section: Measurement Of Oct Functionmentioning
confidence: 99%
“…When the efflux function of MATE was analyzed, it was found that CK2 inhibitor reduced function of MATE1 and the effect of TBBz on MATE2 disappeared, which is in strong contrast to its dramatic up-regulation effect on the uptake function of the transporters, and it was proposed that TBBz may stabilize MATEs in an uptake configuration. Additionally, activators of PKA (forskolin) and PKC (1,2-dioctanoyl-sn-glycerol, DOG) significantly reduced MATE2K efflux function, implicating a regulatory role of these kinases in the process (Kantauskaitė et al, 2020).…”
Section: Slc Family Transportersmentioning
confidence: 99%
“…Both in the liver and at least in the rodent kidneys, OCT1 mediates the first step of organic cation secretion, that is, the uptake of substrates into hepatocytes and into cells of the renal proximal tubules, respectively. For this reason, it should be investigated whether a regulation pathway able to stimulate the second step of secretion process, that is, the excretion of organic cations into the bile and urine, by, for example, the multidrug and toxin extrusion proteins (MATEs) ( Kantauskaite et al, 2020 ), can work together with OCT regulation to globally modulated hepatic and renal substrate secretion.…”
Section: Short-term Regulation Of Organic Cation Transporter 1 Activimentioning
confidence: 99%